Principles of Lifeworld Led Public Health Practice in the UK and Sweden: Reducing Health Inequalities - Ann Hemingway; Liz Norton; Clara Aarts (Hindawi Limited, 2015)
The purpose of this paper is to consider the role of the lifeworld perspective in reducing inequalities in health and we explain how the public health practitioner can use this perspective to address public health issues with individuals and groups. We offer ideas for public health actions that are based on and deal with the lifeworld context of individual people or families. Each of the dimensions of the lifeworld temporality, spatiality, intersubjectivity, embodiment and mood are outlined and their significance explained in relation to health inequalities. Suggestions for action to reduce health inequalities are made and overall principles of lifeworld led public health practice are proposed by way of conclusion. The principles comprise understanding the community members' lifeworld view, understanding their view of their potential, offering resources and facilitating empowerment, and sharing lifeworld case studies and lobbying to influence local and national policy in relation to both the individual and communities.